Tutoria em educação a distância: papeis, formações e percepções - GUIMARÃES, Beatriz Vieira (2015)
Taking in consideration the growing utilization of new communication and information technologies in the teaching scope, more specifically through distance education, this reasearch aims to analyze the teachers training for acting in online teaching, intending to (a) discuss the teacher's role in distance education, (b) analyze tutorship notions from the part of the investigated teachers, (c) identify which abilities were priorized in investigated teachers training and (d) investigate the training's role in the acting of those professionals. These goals were accomplished through bibliographical research and qualitative research made with 14 distance education teachers, which described theirs perceptions about teaching's work and training, for example, through online questionnaires. The theorethical foundation talks in a interdisciplinary perspective with theories in the fields of education, distance euducation, technology and teaching technology. Authors like Lévy (1999), Kenski (2007), Santaella (2003; 2010), Belloni (2008), Paloff and Pratt (1999; 2013) and Tavares (1999; 2001; 2007) based the discussions, and the obtained data were analyzed e discussed baed upon those and another scholars. The collected data analysis showed that the teachers assign mainly as tutorship’s roles the tasks of mediator, encourager, facilitator, motivator and learning promoter, that the pedagogical and social competencies has been more presents in training that technical and management competencies, and that teachers training has been relevant for their professional practice. The expectation with the research results is to contribute for the understanding and enhancement of the training techniques on distance education teachers, including aspects like teaching notions and practices according the teacher's own vision and the needed abilities to the work, among other things, collaborating to the field's enhancement and bringing subsidies in order to rethink and enhance the teacher's training policies.